Disaster Management in Tanzanian Secondary Schools: An Assessment of Disaster Risk Preparedness and Mitigation Strategies - Kambuga, Yusuph Maulid (Journal of Education For Sustainable Innovation, 2023)
This study assessed the disaster risk preparedness in schools and mitigation strategies within school culture's quantitative and qualitative nature. Safety schools ensure high-quality management by implementing effective risk management strategies. To achieve quality education, schools must prioritise disaster risk mitigation strategies. In so doing, three objectives were employed, which include examining the influence of disaster-risk preparedness on school safety measures, assessing teachers' and students' emergency preparedness skills, and evaluating safety equipment availability in schools. The study utilised a mixed-methods approach, encompassing questionnaires, interviews, and physical observations. The research was conducted in the Dodoma region, focusing on five public secondary schools. A total of 152 participants were purposefully and randomly selected for the study. The quantitative data was analysed descriptively, while the qualitative data was thematically paraphrased and presented as quotes. The study further revealed that schools have insufficient safety equipment, leading to unpreparedness during emergencies. Additionally, it was found that teachers and students rarely receive emergency preparedness training, increasing crisis risk in schools. Furthermore, most schools lack essential safety equipment such as fire extinguishers, fire alarms, and fire exits, which puts them at potential disasters.